Development and Validation of Spectrofluorometric Method for the Determination of Ascorbic Acid in Several Dosage Forms by Using Methylene Blue - Benny Permana; Debora Ronauli; Ilma Nugrahani (Acta Pharmaceutica Indonesia, 2021)
Ascorbic acid or vitamin C is one of the most widely consumed supplement and available at the market in several preparations such as tablet, sweetlet, effervescent tablet, and ready to drink product. Spectrofluorometric method has been developed in this study for quantitative determination of ascorbic acid in various forms of products based on the reaction between ascorbic acid and methylene blue. Methylene blue concentration decreased along with the addition of ascorbic acid due to a redox reaction which caused the formation of colorless leuco-methylene blue and dehydroascorbic acid. The fluorescence intensity of methylene blue was measured at excitation and emission wavelengths of 664 nm and 686 nm respectively. The proposed method was found to have a good selectivity, linearity, accuracy, and precision. Validation studies demonstrated a good linearity for the method with a correlation coefficient > 0.999 and Vx0 < 2%. The accuracy test also met the requirements with the recoveries were not less than 90.0% and not more than 110.0%. Precision test gave a relative standard deviation (% RSD) not more than 2%. The ascorbic acid content in several marketed products was evaluated by this new spectrofluorometric method and the result was in good agreement for effervescent tablet, isotonic drink and lozenges with the label claim and specification. Due to its simplicity, the method can be used to analyze vitamin C in different product forms.